Interventions designed to improve uptake of allopurinol for gout treatment in Aotearoa New Zealand: a scoping review - Felicity Goodyear-Smith; Corina Grey; Nicola Dalbeth; Rawiri McKree Jansen; Maryann Heather; Hinamaha Lutui; Siobhan Tu'akoi; Malakai Ofanoa; Samuela Ofanoa (CSIRO Publishing, 2023)
Introduction Gout in Aotearoa New Zealand (NZ) remains an equity issue. The prevalence in Pacific and Māori people is one of the highest internationally. Although Pacific and Māori experience earlier onset and higher burden of gout, which can severely impact their quality of life, their management of it is often sub-optimal. Aim To conduct a scoping review of the NZ literature for interventions to improve the uptake/management of allopurinol for gout and their evaluation. Methods Databases Medline, Scopus, Embase, and CINAHL Plus and the grey literature were searched systematically to identify all NZ intervention studies aiming to improve allopurinol uptake for gout treatment. Interventions included: if they were delivered in NZ, aimed to improve allopurinol uptake, and were provided in English. A narrative approach was used to extract and synthesise data. Results Eighteen peer-reviewed and grey literature publications met the search criteria. Interventions clustered into three domains: multifaceted or multi-practitioner; gout app; and online booklets or fact sheets. Serum urate levels improved in multi-faceted or multi-practitioner interventions only, whereas the gout app only improved patients' awareness and understanding of gout and medications. Online fact sheets and booklets need more active utilisation from health professionals to improve gout health literacy. Discussion Most gout interventions in NZ use multifaceted or multi-practitioner approaches. Although most interventions successfully controlled serum urate levels and improved equitable access for gout patients to urate-lowering therapy, these interventions did not sustain retention, completion, and engagement for certain population groups, particularly Pacific and Māori, who experience a higher burden of gout.